Association of cigarette smoking and physical activity with primary angle closure glaucoma in Malay patients - Salim, Nurul Laila (2017)
INTRODUCTION Primary angle closure glaucoma (PACG) has relatively high prevalence in Southeast Asia and responsible significantly for blindness. This disease is not uncommon among Malays, but there is limited information related to this disease among Malays. At present, the only modifiable risk factor for PACG is intraocular pressure (IOP). Cigarette smoking and physical activities are potential modifiable factors. Previous studies had shown potential association of cigarette smoking and physical activities with oxidative damage, alteration of IOP, and changes of ocular perfusion. These mechanisms may play important role in the pathogenesis of glaucoma. OBJECTIVE To determine the association between smoking and physical activity level and PACG in Malays. METHODOLOGY A cross sectional study was conducted involving 200 Malay PACG patients and 250 control subjects. PACG is diagnosed in the presence of occludable draining angle and features indicating that trabecular obstruction by equivalent to or more than 270° of peripheral iris with evidence of glaucomatous optic disc and visual field damage, based on the World Glaucoma Association consensus. Primary angle closure suspect (PACS), primary angle closure (PAC) and glaucoma suspect patients were excludedfrom the study. Patients with conditions that may affect the visual field such as retinal diseases and neurological diseases were excluded. Those with history of cerebral vascular accident and memory problem including dementia were also excluded. Pedigree chart was also drawn. Those with three generation of Malay lineage without any interracial marriage are included. Face to face interview was conducted to determine the smoking status and physical activity of the recruited patients. Validated questionnaire from Singapore Malay Eye Studies (SiMES) and Bahasa Malaysia version of International Physical Activity Questionnaire (IPAQ) was used. The number of cigarettes smoked per day, frequency and duration of physical activities was also derived from the questionnaires. Univariate analysis was done to identify other risk factors associated with PACG. The association of smoking and physical activity level and PACG was analysed with multiple logistic regression. Confounders such as age, gender, education status, and body mass index were considered in the analysis. RESULTS A total of 255 female and 195 male were included in this study. There was significant difference in sex distribution between PACG patients and control subjects (p<0.001). There was 3.88:1 in female to male ratio among PACG patients. Passive smoking is significantly associated with PACG (p<0.001 OR: 6.82 CI 2.49, 18.67). However, among smokers, the amount of cigarette (p=0.144) and duration of smoking (p = 0.176) is not associated with PACG. Moderate and low physical activity reduces the risk for PACG by 77% (p<0.001, 95% CI 0.10, 0.52) and 79% (p = 0.001, 95% CI 0.09, 0.53) respectively. However, there was no significant difference in days perweek of physical activity (p = 0.861), and minutes per day of physical activity (p = 0.241) between PACG and control subjects. Lower education status is associated with higher risk of PACG. Compared to those with tertiary education, secondary level of education significantly increase the risk for PACG by 9 folds (95% CI 2.67, 33.04) while primary level of education increase the risk for PACG by 18 folds (95% CI 4.53, 73.95) and those without formal education has an increased risk for PACG by 48 folds (95% CI 8.3, 277.99). CONCLUSION Modification of lifestyle may reduce the risk of PACG in Malays. Avoidance of the smoking environment and increase physical activity may prevent the development of PACG in susceptible individual.